2022
DOI: 10.3390/bios12070535
|View full text |Cite
|
Sign up to set email alerts
|

Optical Detection of Fat Concentration in Milk Using MXene-Based Surface Plasmon Resonance Structure

Abstract: MXene (Ti3C2Tx) has emerged very recently as an interacting material for surface plasmon resonance (SPR) configuration. It was discovered that Ti3C2Tx can facilitate the adsorption of biomolecules due to its higher binding energies, stronger interaction between matter and light, and larger surface area. In this work, a two-dimensional Ti3C2Tx and silicon layer-based SPR refractometric sensor is proposed for the sensitive and fast detection of milk fat concentration due to the high significance of this issue to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 50 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Consequently, in the light of the data presented in Table 6, it can be concluded that the performance of the proposed MHS composed of Prism/Ag/AlON/WS 2 /AlON/Sensing medium is better than the contemporary designs as previously reported in ref. 5, 46–48.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, in the light of the data presented in Table 6, it can be concluded that the performance of the proposed MHS composed of Prism/Ag/AlON/WS 2 /AlON/Sensing medium is better than the contemporary designs as previously reported in ref. 5, 46–48.…”
Section: Resultsmentioning
confidence: 99%
“…8 This coupling results in a strong localization of the electric eld called SPR. 9 The change in the refractive index of the analyte alters the wave vector associated with the surface plasmon, which is sensed with the help of the reectance of the TM polarized light. 8,9 The incident angle, which corresponds to the minimum reectance is called the resonance angle, and it is very sensitive to any change in the RI of the sensing medium.…”
Section: Introductionmentioning
confidence: 99%
“…9 The change in the refractive index of the analyte alters the wave vector associated with the surface plasmon, which is sensed with the help of the reectance of the TM polarized light. 8,9 The incident angle, which corresponds to the minimum reectance is called the resonance angle, and it is very sensitive to any change in the RI of the sensing medium. [8][9][10] Therefore, the change in the RI of the sensing medium results in a corresponding change in the reectance dip.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zaky et al [24] proposed a novel biophoton sensor based on porous silicon ternary photonic crystals for more effective detection of fat concentration in milk. Alamwgan et al [25] used surface plasmon resonance structural optics based on MXene to detect fat concentration in milk, which was the first study to apply surface plasmon resonance to detect the fat concentration in milk. Yang et al [26] developed a portable milk composition detector based on an NIR micro-spectrometer, which has driven the development of small spectral instrument equipment.…”
Section: Introductionmentioning
confidence: 99%